DRIVERS INFLUENCING THE USAGE INTENTION TOWARDS ONLINE ZAKAT PAYMENT SYSTEM: EVIDENCE FROM MALAYSIA - Rahman, Rahayu Abdul; Sari, Eka Nurmala; Radzi, Siti Hirdayu Mohd; Saragih, Fitriani; Zakaria, Nor Balkish (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
A digital zakat system significantly enhances zakat collection by streamlining the process, making it more accessible, transparent, and efficient for both zakat payers and zakat institutions. Through digital platforms, individuals can easily calculate, pay, and track their zakat contributions in real time. However, it faces challenges as some zakat payers remain reluctant to use online platforms due to concerns about security and the traditional nature of their giving. Thus, this study investigates how socio-economic determinants, perceived risk, trust in zakat institutions, zakat literacy, and prior experience affect zakat payers' intention to use online zakat payment systems. Data were gathered via an online survey of 288 zakat payers in Malaysia, with cluster sampling used to select participants from government and private sectors across Perak, Selangor, and Kelantan. SmartPLS was used for the analysis. The results indicate that perceived risk has a significant and negative impact on the intention to use online zakat payment services, highlighting the importance of addressing concerns related to risk perception in promoting their adoption. On the other hand, trust in zakat institutions, zakat literacy, and prior experience exhibited positive and significant relationships with zakat payers' intention to utilize online zakat payment services. The findings suggest that institutions mitigate perceived risk, strengthen institutional trust, increase zakat literacy, and leverage users' prior experience to enhance online zakat system adoption. This study contributes significantly to understanding the factors influencing the adoption of online zakat payment services to inform strategies to boost the utilization of online zakat payment services in similar developing country settings.JEL Classification Codes: M430, G32.